2017
DOI: 10.1074/jbc.m117.785477
|View full text |Cite
|
Sign up to set email alerts
|

Role of the disulfide bond in stabilizing and folding of the fimbrial protein DraE from uropathogenic Escherichia coli

Abstract: Dr fimbriae are homopolymeric adhesive organelles of uropathogenic Escherichia coli composed of DraE subunits, responsible for the attachment to host cells. These structures are characterized by enormously high stability resulting from the structural properties of an Ig-like fold of DraE. One feature of DraE and other fimbrial subunits that makes them peculiar among Ig-like domain-containing proteins is a conserved disulfide bond that joins their A and B strands. Here, we investigated how this disulfide bond a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…87˚C, with a free energy of unfolding of 83 kJ mol -1 and a unfolding half-life of 10 8 years at 25˚C [45,46]. We concluded that this high stability, typical for adhesive structures of the chaperone-usher type, is crucial for the maintenance of integrity and functionality of Dr fimbriae [47]. However, colonization of the urinary tract by Dr+ E. coli is equally dependent on the formation of productive bonds between Dr fimbriae and host receptors.…”
Section: Model Of E Coli Dr+ Adherence Under Shear Stressmentioning
confidence: 84%
“…87˚C, with a free energy of unfolding of 83 kJ mol -1 and a unfolding half-life of 10 8 years at 25˚C [45,46]. We concluded that this high stability, typical for adhesive structures of the chaperone-usher type, is crucial for the maintenance of integrity and functionality of Dr fimbriae [47]. However, colonization of the urinary tract by Dr+ E. coli is equally dependent on the formation of productive bonds between Dr fimbriae and host receptors.…”
Section: Model Of E Coli Dr+ Adherence Under Shear Stressmentioning
confidence: 84%
“…There are a great number of theoretical works where the protein folding pathway has been appraised and analyzed, for example, [1]. It was shown that substitutions of amino acid residues, truncation/elongation of the loops and structure elements can affect not only the protein stability but also change completely its folding pathway, i.e., the sequence of formation of different protein regions, for example, [26]. Unfortunately, only few experimental methods and techniques are at hand that allow studying the protein folding pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine residues are present in all the fimbrial subunits of the bcf operon. The role of thiol oxidases in the folding of different fimbrial components is well documented (8,32,51). Moreover, Salmonella has a dedicated thiol oxidase SrgA essential for the biogenesis of Pef fimbriae (5).…”
Section: Bcfh: a Trimeric Protein With Dual Redox Functionmentioning
confidence: 99%